Answer:
![|\alpha| = 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/9e832d3trcrxw9j7t0mosl6jpcoycnsd38.png)
Explanation:
Since
and
are complex conjugates, let's define them as follows:
![\alpha = a+bi](https://img.qammunity.org/2021/formulas/mathematics/high-school/l6ym0qxy27rrf36fw6cl6wbweworupjrrc.png)
![\beta = a-bi](https://img.qammunity.org/2021/formulas/mathematics/high-school/u71kcwf1ko4kvcudczvm7b68oiw73yqbti.png)
![(\alpha)/(\beta^2)=(a+bi)/(a^2-b^2-2abi) =((a+bi)*(a^2-b^2+2abi))/((a^2-b^2-2abi)*(a^2-b^2+2abi)) =(a^3-3ab^2+(3a^2b-b^3)i)/(a^4+2a^2b^2+b^4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/m15mhzqyd45p1o8r6lj1jspu8tsnmazih0.png)
Since
is a real number, complex part of above result must be zero.
![3a^2b-b^3=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/sis0hy9jar8coiiwy2trzwkl1am2526oi1.png)
From to hold above equality,
or
.
However, since
,
![b\\eq 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/7n4tlj331wm6prpvgx0xeo6rons35j6xzv.png)
So,
or
![b =-\sqrt 3 a](https://img.qammunity.org/2021/formulas/mathematics/high-school/6nijirkvll8w7uu2tor5mesb8dhs187p8l.png)
And since
and
are complex conjugates, taking plus or minus sign as found above will not affect the result, so let's write the last version of
and
as follows:
![\alpha = a+\sqrt 3 ai](https://img.qammunity.org/2021/formulas/mathematics/high-school/kl9krnk2ql4vh7upj37ct2pcno9s5iuzoc.png)
![\beta = a-\sqrt 3 ai](https://img.qammunity.org/2021/formulas/mathematics/high-school/j753g13hvsnx2u7ffsn5thqngkh84dldsc.png)
Since
![|\alpha-\beta|=2\sqrt 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/t6lxj5l6cu8kbtpd2mswh8ypf7ara5psrq.png)
⇒
![a = 1](https://img.qammunity.org/2021/formulas/mathematics/high-school/zx8q5yt3x3jl3xgucf8tp2bkofgaqftfni.png)
Finally,
⇒
![|\alpha| = √((1^2+\sqrt 3^2))=2](https://img.qammunity.org/2021/formulas/mathematics/high-school/pn6zwfcdz02ab8q4czdmjw6l11pgvwuw16.png)